2017
DOI: 10.1007/s00705-017-3436-8
|View full text |Cite
|
Sign up to set email alerts
|

Viral polymerase inhibitors T-705 and T-1105 are potential inhibitors of Zika virus replication

Abstract: Since 2015, 69 countries and territories have reported evidence of vector-borne Zika virus (ZIKV) transmission. Currently, there are no effective licensed vaccines or drugs available for the treatment or prevention of ZIKV infection. We tested a series of compounds for their ability to inhibit ZIKV replication in cell culture. The compounds in T-705 (favipiravir) and T-1105 were found to have antiviral activity, suggesting that these compounds are promising candidates for further development as specific antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…During the submission of our manuscript, several groups independently verified anti-ZIKV activities of favipiravir [ 34 , 35 , 36 , 37 ]. Baz et al screened in vitro susceptibility of different strains of ZIKV to favipiravir and ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…During the submission of our manuscript, several groups independently verified anti-ZIKV activities of favipiravir [ 34 , 35 , 36 , 37 ]. Baz et al screened in vitro susceptibility of different strains of ZIKV to favipiravir and ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Favipiravir failed to display anti-ZIKV activity in our assay. Lei Cai et al have showed an EC 50 value above 100 µM (EC 50 was 110.9 ± 13.1 µM) for favipiravir, which was the highest compound concentration in our assay [40]. Thus, antiviral activity might have been observed with increased concentration of favipiravir.…”
Section: Discussionmentioning
confidence: 50%
“…The antiviral spectrum of Xofloza includes seasonal influenza strains and influenza strains resistant to oseltamivir, significantly reducing the viral load compared with oseltamivir [128]. T-705 is a new type of RNA polymerase inhibitor which can inhibit a wide range of viruses by directly entering into the viral RNA chain or by binding directly to the viral RNA polymerase domain to block viral RNA chain replication and transcription [129,130]. It has been approved for listing in Japan [131,132].…”
Section: Treatmentmentioning
confidence: 99%